(untitled) - Huỳnh, Duy Thiện (Cần Thơ, 2019)
In the field of computational chemistry and molecular modelling, this study is to provide more information about the interactions between some novel synthesized benzimidazole derivatives with NS5B polymerase of HCV, thereby evaluating the potential for developing into a novel HCV inhibitor.
Keywords: Chemistry, organic,Hóa học hữu cơ; Synthesis,Tổng hợp